2019
DOI: 10.1111/jmi.12805
|View full text |Cite
|
Sign up to set email alerts
|

On the challenges of greyscale‐based quantifications using X‐ray computed microtomography

Abstract: For X-ray computed microtomography (μ-CT) images of porous rocks where the grains and pores are not fully resolved, the greyscale values of each voxel can be used for quantitative calculations. This study addresses the challenges that arise with greyscale-based quantifications by conducting experiments designed to investigate the sources of error/uncertainty. We conduct greyscale-based calculations of porosity, concentration and diffusivity from various μ-CT experiments using a Bentheimer sandstone sample. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The core structure can be divided into pores and matrix by the binary method through the gray map. Moreover, there are much other information that can be obtained from grayscale CT images, such as local porosity and mass concentration of the transported component ( [29]):…”
Section: Methodologiesmentioning
confidence: 99%
“…The core structure can be divided into pores and matrix by the binary method through the gray map. Moreover, there are much other information that can be obtained from grayscale CT images, such as local porosity and mass concentration of the transported component ( [29]):…”
Section: Methodologiesmentioning
confidence: 99%
“…Detection of void and solid spaces is not an easy procedure in the most of porous material images (Zhang et al, 2019). Gray-level of the images can change between 0 and 1, and determining a certain thresholding level is not viable in many cases due to several reasons including but not limited to:…”
Section: Two-phase Segmentationmentioning
confidence: 99%
“…Detection of void and solid spaces is not an easy procedure in the most of porous material images (Zhang et al., 2019). Gray‐level of the images can change between 0 and 1, and determining a certain thresholding level is not viable in many cases due to several reasons including but not limited to: Low spatial resolution of the images in the presence of micro‐porosity that creates pixels with intensities at the middle of the range (Bultreys et al., 2015) Shadows and artifacts caused by change in the wave speed at the inter‐phase boundary that can lead to overestimate or underestimate the porosity Gradient in the average intensity that prevent using methods, such as global Otsu thresholding (Otsu, 1979) to separate solid and void spaces (Freire‐Gormaly et al., 2015; Iassonov et al., 2009) Reconstruction noises due to the limited projection angles that will add radial artifact shadows to the image known as streaking patterns (Han et al., 2016) …”
Section: Image Segmentationmentioning
confidence: 99%
“…Alqahtani et al [46] used CNNs to estimate porosity, average pore size and specific surface of the porous rocks based on both types of 2-D tomography images and found that binary images could give a more accurate estimation of porous material characteristics compared to the gray-scale ones. However, the morphology of the binarized images is highly dependent on the thresholding technique and it suffers from an inherent uncertainty [63]. In another attempt, Cang et al [64] designed a CNN for prediction of physical properties of heterogeneous materials and successfully predicted the Young modulus, diffusion and permeability of the porous material with more than 90% of certainty on their testing data.…”
Section: Image-based Regression Modelsmentioning
confidence: 99%